Sales activities of Kaymu Bangladesh Limited in relation to the branding and advertising aspect - Ridoy, Reazul Islam (BRAC University, 2017)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2016.